Pengaruh Current Ratio, Debt To Equity Ratio Dan Net Profit Margin Terhadap Harga Saham Perusahaan Sektor Pertambangan Yang Terdaftar Di Bei Tahun 2020-2022 - Alprida Tandi Ayu; Agustinus Mantong; Grace Sriati Mengga (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2023)
This study aims to determine the effect of the current ratio, debt to equity ratio and net profit margin on the share prices of mining companies listed on the Indonesian stock exchange in 2020-2022. The research data were 60 companies and a sample of 5 companies was obtained, using a purposive sampling technique. The data analysis technique used is Simple Linear Regression Analysis and Multiple Linear Regression Analysis. The results showed that the current ratio partially has a significant effect on stock prices, the debt to equity ratio partially has a negative and insignificant effect on stock prices, while the net profit margin partially has a significant effect on stock prices. And simultaneously the current ratio, debt to equity ratio, and net profit margin have a significant effect on stock prices.